Improving Student’s Listening Skill by Using Song at Second Semester of STIE-SAK Academic Year 2021/2022 - Yelnim Yelnim; Sukarta Kartawijaya (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2021)
This research aims to improve the teaching and learning process in the classroom. The researcher would work together with collaborator in order to see the activities that were done during the research. The data used in this research were listening test, fieldnotes and observation form. For the test, it was done at the end of each cycle. Field notes and observation, those were done by the collaborator who helped the research to collect the data. It was taken during the teaching in the class. The participant was the students at second semester of STIE-SAK academic year 2021/2022. There were some classes in the second semester, the sample was taken randomly. Based on the research finding in two cycles, the researcher came to the conclusion because this research was done in two cycles. First, there was a good improvement from students’ test in cycle one and cycle two. Students’ mean score in cycle one was 56, 37 % and increased to 69, 19%. It meant that students’ listening skill was improved after implementing song in teaching English especially in teaching listening at second semester of STIE-SAK especially in the class 2M3 academic year 2021/2022. The students showed positive attitudes towards listening lesson. There are some factors improve student’s listening skill namely song as media improves the students’ interest and motivation, song as teaching media can be implemented with various techniques in teaching learning process, song develops students’ background knowledge, and teaching activities.